Pengaruh Penambahan Serat Baja dan Limbah Kaca Terhadap Kuat Tekan Beton - Mahendra, Rizki; Rahmawati, Cut; zardi, Muhammad (Jurnal Teknik Sipil Unaya, 2025)
This research aims to examine the effect of adding steel fiber and glass waste on the compressive strength of concrete. In this research, steel fiber and glass waste were used as additional ingredients in the concrete mixture with the aim of improving the mechanical properties of concrete, especially compressive strength. The concrete used consists of a mixture of cement, fine aggregate, coarse aggregate, water, as well as variations in the addition of 1% and 2% steel fiber taken from the total weight of cement, split, fine sand and coarse sand. Glass waste in several percentages (5%, 10%, and 15%) based on cement weight. Concrete samples were made and tested at 28 days using the concrete compressive strength testing method in accordance with SNI. The research results showed that the addition of steel fiber and glass waste had an effect on increasing the compressive strength of concrete at a percentage of 1% steel fiber and 15% glass waste. Overall, the use of steel fiber and glass waste can improve the mechanical properties of concrete, provide an environmentally friendly material alternative, and introduce the concept of recycling in construction.